2008
DOI: 10.1016/j.foodchem.2008.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the digestibility of raw and gelatinized potato starches

Abstract: The enzymatic digestibilities of raw and gelatinized starches in various potato starches, as well as sweet potato, cassava, and yam starches, were estimated, along with other starch properties, such as the phosphorus content, median granule size, and rapid visco analyzer (RVA) pasting properties. Furthermore, correlation coefficients were calculated between the hydrolysis rates (HR) by amylase and other starch quality parameters. A larger granule size was closely associated with a lower HR in raw starch, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
79
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 18 publications
17
79
2
Order By: Relevance
“…In contrast to potato peel, the most effective enzymes for the mash were amylase and pectinase, which contain appreciable amylase activity. As raw potato starch is rarely susceptible to digestion without a previ- ous gelatinization treatment (Noda et al, 2008), starch in substandard mash was readily hydrolyzed by the enzymatic reaction due to boiling before the mashing process. The most ethanol (48.6 mg/mL) obtained from the mixture of potato peel and substandard mash was accomplished by the combination of all three enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to potato peel, the most effective enzymes for the mash were amylase and pectinase, which contain appreciable amylase activity. As raw potato starch is rarely susceptible to digestion without a previ- ous gelatinization treatment (Noda et al, 2008), starch in substandard mash was readily hydrolyzed by the enzymatic reaction due to boiling before the mashing process. The most ethanol (48.6 mg/mL) obtained from the mixture of potato peel and substandard mash was accomplished by the combination of all three enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have demonstrated the influence of different nutrients in foods on starch hydrolysis. These nutrients included protein content (Anderson et al, 1981;Chung et al, 2008), moisture content (Lynch et al, 2007), phosphorus content (Noda et al, 2008;Absar et al, 2009) and resistant starch (Frei et al, 2003;Deepa et al, 2010). All these factors had been found to affect starch digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, a fraction of starch, which is defined as resistant starch, is not digested in the small intestine and reaches the large intestine, where it is hydrolysed and fermented by microorganisms. Potato starch (PS) is 20% amylose, which has large granules and a B-crystalline structure that is not generally accessible to digestive enzymes (Champ and Colonna, 1993;Noda et al, 2008). In vitro hydrolysis of raw potato starch with amylolytic enzymes showed significant resistance to these enzymes (Lee et al, 1985;Bauer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%